An Upper Bound of the Bezout Number for Piecewise Algebraic Curves over a Rectangular Partition - Feng-Gong Lang; Xiao-Ping Xu (International Journal of Mathematics and Mathematical Sciences)
A piecewise algebraic curve is a curve defined by the zero set of a bivariate spline function. Given two bivariate spline spaces (Δ) over a domain D with a partition Δ, the Bezout number BN(m,r;n,t;Δ) is defined as the maximum finite number of the common intersection points of two arbitrary piecewise algebraic curves (Δ). In this paper, an upper bound of the Bezout number for piecewise algebraic curves over a rectangular partition is obtained.